The Photolanguage method in the treatement field - Μητσοπούλου - Σόντα Λίλα; Ναυρίδης Κλήμης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
In this article we present a particular method of group psychoanalytic psychotherapy, which is included in methods using mediating objects as the Photolanguage© method. We propose clinical sequences from the case of Sophie who participates in a Photolanguage© group in order to illustrate in a better way the method but the specific processes which take place too. Sophie, whose metaphorical thought is failing, has the possibility to access consciousness and subjectivity with the double aid of the group and of the mediating object. The figurability of the affect can be treated by the group which proposes a space where the internal groups of Sophie can be diffracted, permitting her to find the words and restore the thread of her personal history. The photograph, as an object, creates a playing area where the subject is able to create the link between her internal and external images, and between sensations and words.